PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM PENINGKATAN KUALITAS PEMBELAJARAN GURU DI SEKOLAH DASAR NEGERI 1 BABAKTULUNG - Yulianto Hery Purnomo; Soedjono (STKIP Subang, 2024)
The study explores the role of school principals as supervisors in improving the quality of teaching at SD Negeri 1 Babaktulung. Utilizing a qualitative approach, the research examines how supervision strategies influence pedagogical practices, professional development, and social competencies of teachers. Data were collected through interviews, observations, and document analysis, with findings triangulated to enhance validity. The study highlights that effective supervision fosters teaching innovation, enhances teacher competencies, and increases student engagement. Key challenges, such as limited resources and resistance to supervision, are addressed through collaborative strategies and targeted professional development. The key results of the research are as follows: (1) Supervisory practices increased the use of innovative teaching methods, such as project-based learning and group discussions. (2) Teachers demonstrated enhanced pedagogical and professional competencies, particularly in integrating technology into teaching. (3) Student engagement improved significantly through active participation in interactive and technology-supported learning activities. The results underline the transformative potential of supervisory practices in elementary education, providing actionable recommendations for stakeholders.